The humanitarian development paradigm search global justice - David, Wilfred L. (New York University Press of America, 2004)
In Humanitarian Development Paradigm, Wilfred L. David makes a plea for the fundamental reorientation of the economics that guide conventional development discourse, moving toward an emancipatory conversation focusing on human well-being or people-centered liberation. His paradigm-altering vision elevates core human values, guaranteed rights, and global justice in development thinking, practice, and policy.
Includes index
Keywords: Development